Synthesis, Characterization, and Biological Evaluation of a Dual‐Action Ligand Targeting αvβ3 Integrin and VEGF Receptors1. Issue 5 (2nd July 2015) - Zanella, Simone; Mingozzi, Michele; Dal Corso, Alberto; Fanelli, Roberto; Arosio, Daniela; Cosentino, Marco; Schembri, Laura; Marino, Franca; De Zotti, Marta; Formaggio, Fernando; Pignataro, Luca; Belvisi, Laura; et al.
Abstract A dual‐action ligand targeting both integrin αVβ3 and vascular endothelial growth factor receptors (VEGFRs), was synthesized via conjugation of a cyclic peptidomimetic αVβ3 Arg‐Gly‐Asp (RGD) ligand with a decapentapeptide. The latter was obtained from a known VEGFR antagonist by acetylation at the Lys13 side chain. Functionalization of the precursor ligands was carried out in solution and in the solid phase, affording two fragments: an alkyne VEGFR ligand and the azide integrin αVβ3 ligand, which were conjugated by click chemistry. Circular dichroism studies confirmed that both the RGD and VEGFR ligand portions of the dual‐action compound substantially adopt the biologically active conformation. In vitro binding assays on isolated integrin αVβ3 and VEGFR‐1 showed that the dual‐action conjugate retains a good level of affinity for both its target receptors, although with one order of magnitude (10/20 times) decrease in potency. The dual‐action ligand strongly inhibited the VEGF‐induced morphogenesis in Human Umbilical Vein Endothelial Cells (HUVECs). Remarkably, its efficiency in preventing the formation of new blood vessels was similar to that of the original individual ligands, despite the worse affinity towards integrin αVβ3 and VEGFR‐1.